2008
DOI: 10.1080/14622200802238860
|View full text |Cite
|
Sign up to set email alerts
|

In sight, in mind: Retailer compliance with legislation on limiting retail tobacco displays

Abstract: We investigated retailer compliance with point-of-sale display legislation, using a New Zealand region as a case study. An observational survey was conducted of nonspecialist tobacco retailers in the lower North Island of New Zealand during 2006. Compliance was assessed in relation to store type (dairies, convenience stores, supermarkets, and service stations) and by characteristics of the population of the census area unit in which the store was situated. These characteristics include the level of socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…29 Researchers studying compliance have suggested that the display ban could produce even larger decreases in youth smoking with better enforcement. 30 Although much progress has been made both nationally and in NYC, smoking persists at significant levels among teens. Implementation and enforcement of polices that reduce the impact of tobacco product promotion in retail settings could play an important role in efforts to curtail smoking among this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Researchers studying compliance have suggested that the display ban could produce even larger decreases in youth smoking with better enforcement. 30 Although much progress has been made both nationally and in NYC, smoking persists at significant levels among teens. Implementation and enforcement of polices that reduce the impact of tobacco product promotion in retail settings could play an important role in efforts to curtail smoking among this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…23,[28][29][30] Evaluations of these restrictions provide evidence for the potential benefits of keeping PoS displays out of sight. For example, following a ban on PoS display in Ireland in 2009, the number of youths overestimating how many of their peers smoke regularly declined by nearly 30 %.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco industry adopts such tactics globally; tobacco products and advertisements are often placed near candies and children's items at the front of the store and on counter tops, encouraging children to see them as harmless everyday items (Feighery et al, 2001;Quedley et al, 2008;Barnoya et al, 2010). Tobacco products often occupy large and prominent display space in stores and are strategically designed to encourage impulse purchasing and promote certain brands while making health warnings less visible (Quit Victoria, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO, fewer than half of all countries with a ‘comprehensive’ ban have achieved high compliance, 14 which suggests that more progress has been made towards enacting marketing restrictions than enforcing them. Poor compliance with marketing restrictions documented in the USA and other high-resourced countries 8587 illustrate significant challenges for tobacco control. For example, California pursued successful enforcement action against several tobacco company violations, such as distributing free tobacco products at sporting events where minors competed and mailing free cigarettes to individuals' homes.…”
Section: Implications For Policy and Practicementioning
confidence: 99%